2020
DOI: 10.1038/s10038-020-0806-y
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to participate in genome testing: a survey of public attitudes from Qatar

Abstract: Genomics has the potential to revolutionize medical approaches to disease prevention, diagnosis, and treatment, but it does not come without challenges. The success of a national population-based genome program, like the Qatar Genome Program (QGP), depends on the willingness of citizens to donate samples and take up genomic testing services. This study explores public attitudes of the Qatari population toward genetic testing and toward participating in the QGP. A representative sample of 837 adult Qataris was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 18 publications
5
35
0
Order By: Relevance
“…In terms of genetic literacy in Singapore, we report an average genetic literacy score that may indicate a need for more public education and engagement programs on genetics and participation in PM projects. This level of literacy is similar to survey findings recently reported from Qatar [ 19 ], where 51.6% of the participants scored “high” for genetic literacy. The same study found that amongst respondents with a high level of basic literacy in genetics, 76.4% expressed willingness to participate in the Qatar Genome Programme activities, suggesting genetic literacy may be a factor affecting enrolment rates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of genetic literacy in Singapore, we report an average genetic literacy score that may indicate a need for more public education and engagement programs on genetics and participation in PM projects. This level of literacy is similar to survey findings recently reported from Qatar [ 19 ], where 51.6% of the participants scored “high” for genetic literacy. The same study found that amongst respondents with a high level of basic literacy in genetics, 76.4% expressed willingness to participate in the Qatar Genome Programme activities, suggesting genetic literacy may be a factor affecting enrolment rates.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have highlighted the importance of genetic literacy with regard to public attitudes toward participation in genomics research. A recent study of Qatari citizens [ 19 ], for example, found that willingness to participate in genome projects is linked with basic literacy in genetics, prior experience with genetic testing, and a family history of genetic diseases. A UK-based study [ 20 ] found that genetics education, familiarity with science, technology, engineering, math or medicine (STEMM), and gender were all significant variables influencing data sharing preferences.…”
Section: Introductionmentioning
confidence: 99%
“…The observed association with university education is in harmony with a study that was conducted in Saudi Arabia [5] and Turkey [26]. The impact of education on the willingness to undergo genetic testing, in general, is well documented [32-35]. Therefore, enhancing awareness about the importance of genetic testing can improve the acceptance of PGS in the populations.…”
Section: Discussionsupporting
confidence: 71%
“…These Arab genome programs have overcome the obstacles and limitations on collecting samples. The Program SHGP, KGP, QGP, EGP and BGP are visionary projects on human genomics with the vision to detect and prevent genetic diseases in the Kingdom of Saudi Arabia (KSA), the State of Kuwait, the State of Qatar, the United Arab Emirates (UAE) and the Kingdom of Bahrain, respectively to establish worldclass facility on genomic research in the Arab ancestry [2][3][4][5][6]. The SHGP was implemented by King Abdulaziz City for Science and Technology, on its way to reach sequence 100,000 human genomes in Saudi Land to achieve gold standard findings in the Saudi population on genomics-based biomedical research [2].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reviews on population structure and prevalent genetic disorders can help to understand the initial studies on Mendelian genes and P r e p r i n t associated traditions in the high consanguineous community of Kingdom of Saudi Arabia and other Arab populations [10][11][12]. The State of Qatar, which is located in the Arabian Gulf established the QGP (https://www.qatargenome.org.qa/), a Qatari population-based genome initiative aimed at sequencing the complete genomes of a large part of the Qatari population, began its pilot phase in 2015 [3]. The Kuwait Genome Project (KGP) is a high-coverage effort to sequence Kuwaiti genomes from genetically different subgroups of Kuwaitis [4].…”
Section: Introductionmentioning
confidence: 99%